Longitudinal quantitative assessment of coronary atherosclerosis related to normal systolic blood pressure maintenance in the absence of established cardiovascular disease. Issue 8 (8th June 2022) - Won, Ki‐Bum; Park, Hyung‐Bok; Heo, Ran; Lee, Byoung Kwon; Lin, Fay Y.; Hadamitzky, Martin; Kim, Yong‐Jin; Sung, Ji Min; Conte, Edoardo; Andreini, Daniele; Pontone, Gianluca; Budoff, Matthew J.; et al.
Abstract: Background: Atherosclerosis‐related adverse events are commonly observed even in conditions with low cardiovascular (CV) risk. Longitudinal data regarding the association of normal systolic blood pressure maintenance (SBPmaintain ) with coronary plaque volume changes (PVC) has been limited in adults without traditional CV disease. Hypothesis: Normal SBPmaintain is important to attenuate coronary atherosclerosis progression in adults without baseline CV disease. Methods: We analyzed 95 adults (56.7 ± 8.5 years; 40.0% men) without baseline CV disease who underwent serial coronary computed tomographic angiography with mean 3.5 years of follow‐up. All participants were divided into two groups of normal SBPmaintain (follow‐up SBP < 120 mm Hg) and ≥elevated SBPmaintain (follow‐up SBP ≥ 120 mm Hg). Annualized PVC was defined as PVC divided by the interscan period. Results: Compared to participants with normal SBPmaintain, those with ≥elevated SBPmaintain had higher annualized total PVC (mm 3 /year) (0.0 [0.0–2.2] vs. 4.1 [0.0–13.0]; p  < .001). Baseline total plaque volume ( β  = .10) and the levels of SBPmaintain ( β  = .23) and follow‐up high‐density lipoprotein cholesterol ( β  = −0.28) were associated with annualized total PVC (all p  < .05). The optimal cutoff of SBPmaintain for predicting plaque progression was 118.5 mm Hg (sensitivity: 78.2%, specificity: 62.5%; area under curve: 0.700; 95% confidence interval [CI]: 0.59–0.81; p  < .05). SBPmaintain  ≥ 118.5 mm Hg (odds ratio [OR]: 4.03; 95% CI: 1.51–10.75) and baseline total plaque volume (OR: 1.03; 95% CI: 1.01–1.06) independently influenced coronary plaque progression (all p  < .05). Conclusion: Normal SBPmaintain is substantial to attenuate coronary atherosclerosis progression in conditions without established CV disease.